The value of environmental communication research - Brevini, Benedetta (International Communication Gazette, 2016)
Is environmental communication research returning something of value to society? Is it interdisciplinary enough? This article charts the recent rise and development of environmental communication, its successes and failures to produce public value. As the environmental crisis is the most crucial social and political issue of our time, there is a pressing need for environmental communication to engage with questions that are already familiar to scholars in media studies: questions about inequalities in power and resources – specifically among the gatekeepers influencing and shaping environmental communication – but also questions about the materiality of communication systems as environmentally hazardous machines.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzQ4MDQ4NTE2NjU1NzI4